Fatigue characteristics of stone mastic asphalt mix reinforced with fiber glass - Mahrez, A.; Karim, Mohamed Rehan (Academic Journals, 2010)
Asphalt modification/reinforcement has received considerable attention as viable solutions to enhance flexible pavement performance. This is mainly prompted by the unsatisfactory performance of traditional road materials exposed to dramatic increases and changes in traffic patterns. This paper presents the characteristics and properties of glass fiber reinforced Stone Mastic Asphalt. Laboratory tests were conducted to evaluate such related properties of asphalt mixture with different fiber contents. The tests undertaken comprise the Marshall test, indirect tensile test, creep test and fatigue test using repeated load indirect tensile test. The results showed that the addition of fiber does affect the properties of bituminous mixes, by decreasing its stability and increasing the voids in the mix. Stiffness properties of reinforced SMA mix were enhanced by about 12 as compared to control mix. Mixes with more than 0.2 fiber content exhibited lower resistance to permanent deformation. The results indicated that the fiber has the potential to resist structural distress that occur in road pavement as result of increased traffic loading, thus improving fatigue life by increasing the resistance to cracking and permanent deformation especially at higher stress level.